2017
DOI: 10.1121/1.5007730
|View full text |Cite
|
Sign up to set email alerts
|

Auditory memory for random time patterns

Abstract: The acquisition of auditory memory for temporal patterns was investigated. The temporal patterns were random sequences of irregularly spaced clicks. Participants performed a task previously used to study auditory memory for noise [Agus, Thorpe, and Pressnitzer (2010). Neuron 66, 610-618]. The memory for temporal patterns displayed strong similarities with the memory for noise: temporal patterns were learnt rapidly, in an unsupervised manner, and could be distinguished from statistically matched patterns after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(86 citation statements)
references
References 46 publications
8
75
3
Order By: Relevance
“…In contrast, here we focus on fast memory formation for sequences of discrete tones, distinguishable only by their specific order, and presented in a surrounding context of highly similar patterns (all sequences consisted of the same 20 'building blocks'). We showed that the vast majority of patterns were learned, revealing high sensitivity to reoccurring arbitrary frequency patterns despite the exceedingly rare reoccurrence rate (every ~2.7 minutes; 5% of trials; in contrast to the much more frequent reoccurrence (< ~15 seconds) in Agus et al (2010) and Kang et al (2017).…”
Section: Relationship To 'Noise Memory'mentioning
confidence: 90%
See 4 more Smart Citations
“…In contrast, here we focus on fast memory formation for sequences of discrete tones, distinguishable only by their specific order, and presented in a surrounding context of highly similar patterns (all sequences consisted of the same 20 'building blocks'). We showed that the vast majority of patterns were learned, revealing high sensitivity to reoccurring arbitrary frequency patterns despite the exceedingly rare reoccurrence rate (every ~2.7 minutes; 5% of trials; in contrast to the much more frequent reoccurrence (< ~15 seconds) in Agus et al (2010) and Kang et al (2017).…”
Section: Relationship To 'Noise Memory'mentioning
confidence: 90%
“…Inspections of the nature of this memory revealed that it was robust to time reversal, and even to scrambling into bins as small as 10-20 ms (Agus, Thorpe, & Pressnitzer, 2010;Viswanathan, Rémy, Bacon-Macé, & Thorpe, 2016), indicating that the remembered features reflect local spectrotemporal idiosyncrasies within the reoccurring noise snippet. The apparent dependence of this memory on certain local features of the noise signal may also explain the high inter-sample variability often seen with this paradigm (i.e., the distinction between 'memorable' and 'not memorable' patterns; Agus et al, 2010;Viswanathan et al, 2016;Kang et al, 2017).…”
Section: Relationship To 'Noise Memory'mentioning
confidence: 99%
See 3 more Smart Citations